Pengaruh Social Support Dalam Work Family Conflict Terhadap Tingkat Stres Kerja - Muhammad Alfan Fauzi; Devanggi Putri Ramadhani; Riyan Sisiawan Putra (Jurnal Multidisiplin Madani, 2022)
The purpose of this literature study is to investigate the role of social support correlation between work-family conflict on job stress. The literature study was based on 17 empirical studies from any national and international journals. Data collected by using search engine methods. The results suggest that work-family conflict had a positive relationship with job stress. Enacting dual social support (work and nonwork-related social support) can be a positive resource for reducing the adverse effects of job stress and work-family conflict effectively. Based on empirical studies, also found social support can be the best viewed as a moderator to a perceived stressor and work- family conflict